1999
DOI: 10.1029/1999gl900027
|View full text |Cite
|
Sign up to set email alerts
|

Type I PSC‐particle properties: Measurements at ALOMAR 1995 to 1997

Abstract: Abstract. Polar stratospheric clouds (PSC) were observed above Andehes, Norway (69øN, 16øE) with the ALOMAR Rayleigh/Mie/Raman-Lidar during three winters and with an optical particle counter on two occasions. Multiwavelengths measurements allow the derivation of the parameters of a monomodal particle size distribution and the derivation of volume densitiespaper if the refractive index is known. The particle counter results are used to determine the best refractive index value. The relation of volume density to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“… Stein et al [1999] observed Type Ib during 0100–0600 UT of 17 January at altitudes of 21.5–24 km, and mixtures of Type Ia and Ib during 1400–2300 UT of 19 January 1997 at the altitude range of 20–23 km at Sodankyla, Finland (67°N, 26°E). Mehrtens et al [1999] obtained a better agreement with NAT rather than STS for PSC layers observed at Andenes, Norway (69°N, 16°E) from 18 to 24 km on 19 January 1997. Reichardt et al [2000] observed PSC Ib near 22 km and PSC Ia near 24 km at Esrange, Sweden (67.9°N, 21.1°E) for two hours from 1700 UT on 20 January 1997.…”
Section: Comparison With Other Reportsmentioning
confidence: 74%
See 1 more Smart Citation
“… Stein et al [1999] observed Type Ib during 0100–0600 UT of 17 January at altitudes of 21.5–24 km, and mixtures of Type Ia and Ib during 1400–2300 UT of 19 January 1997 at the altitude range of 20–23 km at Sodankyla, Finland (67°N, 26°E). Mehrtens et al [1999] obtained a better agreement with NAT rather than STS for PSC layers observed at Andenes, Norway (69°N, 16°E) from 18 to 24 km on 19 January 1997. Reichardt et al [2000] observed PSC Ib near 22 km and PSC Ia near 24 km at Esrange, Sweden (67.9°N, 21.1°E) for two hours from 1700 UT on 20 January 1997.…”
Section: Comparison With Other Reportsmentioning
confidence: 74%
“…It is assumed that the PSC size distribution can be represented by a single mode lognormal distribution given by the expression where N is the total number density (particles cm −3 ), R is the median radius (μm), and σ is the geometric mean standard deviation (dimensionless) of r . The single mode distribution has been used in the analysis of lidar measurements of PSCs (see similar study by Dye et al [1992], Mehrtens et al [1999], and Toon et al [2000]). As noted above, the ratio of the theoretical extinction coefficients at two wavelengths, λ i and λ j , is defined as the theoretical relative extinction coefficient, α cal (λ i , λ j ).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…If the sizes of the scattering particles are comparable to the wavelength of the radiation used for the observation, one can exploit the wavelength dependence of the cloud optical properties to gain insight into the microphysics of the particulate scatterers. Over the years, sophisticated lidar instrumentation and retrieval algorithms have been developed for this purpose that have been successfully applied to stratospheric aerosols [ Del Guasta et al , 1994; Wandinger et al , 1995], polar stratospheric clouds [ Carslaw et al , 1998; Mehrtens et al , 1999], tropospheric aerosols [ Müller et al , 1998, 2001], and contrails [ Sassen et al , 2001]. …”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we explore an alternative method based on the comparison between measured and model-simulated Backscatter Coefficients (BC), using a Monte Carlo approach. The formulation of the method is inspired by the works of Beyerle et al (1994) and Mehrtens et al (1999). The retrieval algorithm minimizes a cost function of the misfit between measurements and model simulations with the control variables being the parameters of the PSC size distribution.…”
mentioning
confidence: 99%